Organ-level distribution tandem mass spectrometry analysis of three structural types of brassinosteroids in rapeseed - Tong, Jianhua; Zhao, Wenkui; Wang, Keming; Deng, Danyi; Xiao, Langtao (Frontiers in Plant Science, 2024)
Brassinosteroids (BRs) are a class of naturally occurring steroidal phytohormones mediating a wide range of pivotal developmental and physiological functions throughout plant's life cycle. Therefore, it is of great significance to determine the content and the distribution of BRs in plants.Regretfully, although a large number of quantitative methods for BRs by liquid chromatograph-mass spectrometry (LC-MS/MS) have been reported, the in planta distribution of BRs is still unclear because of their lower contents in plant tissues and the lack of effective ionizable groups in their chemical structures. In this study, we established a novel analytical method of BRs based on C18 cartridge solid-phase extraction (SPE) purification, 4-dimethylaminophenylboronic acid (DMAPBA) derivatization and online valve-switching system coupled with ultra-high performance liquid chromatography-electrospray ionization-triple quadrupole mass spectrometry (UHPLC-ESI-MS/MS). This method has been used to quantify three structural types of BRs (epibrassinolide, epicastasterone and 6-deoxo-24-epicastasterone) in different organs of Brassica napus L. (rapeseed). We found that the contents of three BRs in plant 删除[赵畅宇妈妈]: flowers were the highest, followed by tender pods. The levels of three BRs all decreased during the maturation of the organs. Based on the organ-level distribution of BRs in rapeseed, the spatial distribution maps of three BRs in rapeseed were outlined for the first time. Our results provided useful information for the precise in-situ localization of BRs in plants and the metabolomic research of BRs in future work.